2013
DOI: 10.11648/j.avs.20130106.11
|View full text |Cite
|
Sign up to set email alerts
|

Breed and Season Effects on the Claw Lesions of Dairy Cows in Ardebil, Iran

Abstract: Seasonal and breed effects on the prevalence and type of claw lesions were investigated on 24854 cases of culled cows at central abattoir in the vicinity of Ardebil in Iran during twelve consecutive months. After recording information for each case, the feet were amputated and ground surface of the claws were pared for more morphopathological study. The prevalence rate of claw lesion among all cases was 24.2 per cent. The claws lesion in local cows (24.4 %) was more than imported Holstein cows (22.5 %) (P< 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
1
2
Order By: Relevance
“…This study was performed on hoof and digit lesions of slaughtered cattle. Our findings showed that 61.5% of the cattle examined had at least one lesion in their feet, which is much higher than that of the results of a similar study in the neighbour province, Ardabil, reporting 24.2% of slaughtered cases had hoof lesions (15). Given that in the surveyed geographical area, cattle are usually culled if keeping them is not justified because of low milk yield or lameness, it is likely that the prevalence of lameness in the livestock population of the area is less than our finding.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This study was performed on hoof and digit lesions of slaughtered cattle. Our findings showed that 61.5% of the cattle examined had at least one lesion in their feet, which is much higher than that of the results of a similar study in the neighbour province, Ardabil, reporting 24.2% of slaughtered cases had hoof lesions (15). Given that in the surveyed geographical area, cattle are usually culled if keeping them is not justified because of low milk yield or lameness, it is likely that the prevalence of lameness in the livestock population of the area is less than our finding.…”
Section: Discussioncontrasting
confidence: 80%
“…Cattle that are in the pasture during the day and are housed in the stall at night are also at greater risk of developing the lesion than those are in the pasture all the time (25); therefore, it seems that this factor, as well as the inappropriate floor of the stalls, caused 7.75% of white line disease in this study. Although, the prevalence of this lesion in a similar study in Ardabil was higher (25.1%) than our findings, which may also be related to the differences in moisture (15).…”
contrasting
confidence: 94%
“…In addition to, Pinedo and de Vries (2010) and Miller et al (2008) indicated that calving in hot season (spring and summer) increased the risk of cows leaving the herd compared to calving in cool season (fall and winter). One of the reasons for increasing the risk of cows leaving the herd in hot season (spring and summer) may be increase the incidence of some disorders such as claw lesions (Madadzadeh et al, 2013). On the other hand, increasing the risk of cows leaving the herd in hot season (spring and summer) may also be related to the influence of seasonal characteristic differences on cow health, milk production level, feed availability, milk price, conception rate and profitability (Delorenzo et al, 1992;Hadley et al, 2006).…”
Section: Calving Seasonmentioning
confidence: 99%